2007
DOI: 10.2320/matertrans.mra2007098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron and/or Carbon on the Grain Refinement of Mg-3Al Alloy

Abstract: The effect of iron on the grain refinement of Mg-3Al alloy modified with and without carbon powder has been investigated in the present study. Significant grain refinement could be obtained for Mg-3mass%Al alloy modified with either Fe or carbon. The Al-C-O and Al-Fe particles were observed which should be the potent nuclei for Mg grains. The high segregating power of Fe was also proved as an important factor which determines the grain size of Mg-Al alloys. Refining efficiency could be further obtained by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…A large amount of Al-C-O-Ca-rich intermetallic particles were found in the sample of the Mg-3Al alloy refined by the combination of 0.2% C and 0.5% Ca. In our other researches [27,28], the Al-C-O particles were transformed into Al-C-O-Fe-rich and Al-C-O-Mn-rich intermetallic particles despite a little amount (0.2%) of Fe or Mn addition. In fact, the intermetallic compounds containing Al and alloying elements (such as Al-Ca, Al-Fe, Al-Mn, etc.)…”
Section: Discussionmentioning
confidence: 98%
“…A large amount of Al-C-O-Ca-rich intermetallic particles were found in the sample of the Mg-3Al alloy refined by the combination of 0.2% C and 0.5% Ca. In our other researches [27,28], the Al-C-O particles were transformed into Al-C-O-Fe-rich and Al-C-O-Mn-rich intermetallic particles despite a little amount (0.2%) of Fe or Mn addition. In fact, the intermetallic compounds containing Al and alloying elements (such as Al-Ca, Al-Fe, Al-Mn, etc.)…”
Section: Discussionmentioning
confidence: 98%
“…The element of Fe was proved to be an important factor to determine the refining efficiency for the Mg-Al alloys refined by carbon inoculation [21][22][23][24]. Discrepant results that whether Fe inhibits the grain refinement or not were obtained by some researchers [21][22][23][24].…”
Section: Introductionmentioning
confidence: 84%
“…Discrepant results that whether Fe inhibits the grain refinement or not were obtained by some researchers [21][22][23][24]. Haitani et al [21] concluded firstly that Fe was an inhibiting element for grain refinement, since it poisoned the potency of the Al 4 C 3 nucleating particles by transforming Al 4 C 3 into Al-C-Ferich intermetallic compounds.…”
Section: Introductionmentioning
confidence: 93%
“…However, Pan et al [15] insisted that Fe played an important role in the formation of the nucleating particle rather than an inhibiting element. In our previous study, further grain refining efficiency could be obtained for the Mg-3Al alloy modified by the combination of carbon and Fe [22]. It is very difficult to understand clearly why contradictory conclusions were made for the same phenomenon.…”
Section: Introductionmentioning
confidence: 87%